أثر التحفيز على الرضا الوظيفي من خلآل العدالة التنظيمية بالتطبيق على المديريات العامة للتربية والتعليم بسلبنة عمان - Fatma Hamed Mohammed Alnaimi
The study aims to analyze the effects of motivation on achieving job satisfaction, and the extent of effect of organizational justice on the relationship of motivation with job satisfaction as a moderator by applying it to the general directorate of education in the Sultanate of Oman. To achieve the objectives of the study, the descriptive and analytical approach is used to examine the hypotheses and verify the extent of correlation of such variables among themselves based on the study instrument, the questionnaire. The instrument was designed based on the literature of each variable and was modified to suit the current study. The questionnaire was distributed to a stratified random sample of 381 individuals from the general directorates of education. The hypotheses were measured and analyzed using the Structural Equation Modeling (SEM) using AMOS. The results showed that there is a direct and positive effect of motivation on achieving job satisfaction, as the values of the standard ratings indicated that paying attention to offering moral incentives would contribute by 40% to achieving job satisfaction, and that paying attention to offering material incentives would contribute by 60% to achieving job satisfaction. The study concluded that moral incentives have a positive effect on the dimensions of job satisfaction (leadership style, promotion and development opportunities, and work environment), and that material incentives have a positive and direct effect on the dimensions of job satisfaction (Leadership style, work content, promotion and development opportunities, and work environment). The study also concluded that there are morally significant differences of the effect of organizational justice on the relationship between motivation and job satisfaction in favor of the sample that supports organizational justice in the general directorates in this study. In light of the results of the study, the researcher presented some recommendations including designing an incentive program with clear and scientific standards suitable for the educational work environment, and to assure that the incentive program is activated in the directorates of education objectively and fairly among the staff based on the standards of performance and the efforts invested so that the staff excel through the incentives according to their performance, thus ensuring a higher job satisfaction, performance and a better productivity.